Revised terminal half‐life of nonacog alfa as derived from extended sampling data: A real‐world study involving 64 haemophilia B patients on nonacog alfa regular prophylaxis. Issue 4 (14th April 2022) - Tardy, Brigitte; Lambert, Thierry; Chamouni, Pierre; Montmartin, Aurélie; Trossaert, Marc; Claeyssens, Ségolène; Berger, Claire; Ardillon, Laurent; Gay, Valérie; Delavenne, Xavier; Harroche, Annie; Chelle, Pierre
Abstract: Background: Nonacog alfa, a standard half‐life recombinant factor IX (FIX), is used as a prophylactic treatment in severe haemophilia B (SHB) patients. Its half‐life determined in clinical studies involving a limited sampling (72 h) was shown to be rather short. In our clinical practice, we suspected that its half‐life could have been underestimated. Objectives: We aimed to evaluate nonacog alfa pharmacokinetics in real world clinical practice based on FIX levels in patients receiving prophylaxis. Methods: We retrospectively collected data on patients with SHB receiving prophylaxis from eight centres across France. The terminal half‐life (THL), time to reach 5–2 IU/dl and FIX activity at 48, 72 and 96 h were derived by Bayesian estimations using NONMEM analysis. Results and conclusions: Infusion data ( n = 455) were collected from 64 patients with SHB. The median THL measured in 92 pharmacokinetic (PK) studies was 43.4 h. In 26 patients ≤12 years of age, 51 PK studies showed a median time to reach 5 IU/dl of FIX of 70.5 h and a median time to reach 2 IU/dl of 121.5 h. In 38 patients 13–75 years of age, 41 PK studies showed a median time to reach 5 IU/dl of FIX of 92.0 h and a median time to reach 2 IU/dl of 167.5 h. Extending the sampling beyond 72 h makes it possible to observe a plateau, with FIX remaining between 2 and 5 IU/dl for several days and shows that the THL of nonacog alfa might be longer than previously described. Essentials: Nonacog alfa terminal half‐life (THL) in patients receiving regular prophylaxis was evaluated in clinical practice. The median THL was estimated to be 36.9 h for patients aged .8–12 years. The median THL was estimated to be 49.9 h for patients aged 13–75 years. For patients aged ≤12 and >12 years, the median times to reach 5 IU/dl were 70.5 and 92 h, respectively; to reach 3 IU/dl, 95.5 and 131.5 h, respectively; to reach 2 IU/dl, 121.5 and 167.5 h, respectively. We suggest that the half‐life of nonacog alfa might be longer than previously described in both younger and older patients.